Revisiting Midnight's Children: Critical Disability and Postcolonial Studies Interventions in Christology. Issue 3 (3rd September 2015) - Betcher, Sharon
Abstract : Within postcolonial literature, "Midnight's Children" (Rushdie) their births laden not only with supernatural expectation, but traumatically marked with cultural upheaval—appear as symbols of hope in an unreliable future. Given the presence of disability in postcolonial literature, this essay pushes Christian theology to think with our own "midnight's child"—one born "uncomely, " disfigured (Isaiah 53). "Disability"— never without some material signature, but always a cultural representation— names the ply of rhetoric batted back and forth between colonial and anti-colonial, these volleys shifting aesthetics and bending arcs of affect. Through the optics of modern realism, Jesus appeared as healer for the regime of "ablenationalism." This essay, however, dares to think the figure of Jesus as volleyed back at Empire by anti-colonials. Reading with the Global South—namely, with the biblical scholar Simon Samuel and the constructive theology of Marcella Althaus-Reid—makes the figure of Jesus as postcolonial crip not wholly unprecedented.